Role of insulin and insulin-like peptides in bone formation: identification of bone-specific target genes and regulatory mechanisms, and characterization of the insulin-mimetic effect of vanadium - Tiago, Daniel (2011)
Tese de Doutoramento em Biologia, Especialidade em Biologia Molecular, Universidade do Algarve, 2008